Comparison of Dabigatran and Warfarin in Patients With Atrial Fibrillation and Valvular Heart Disease: The RE-LY Trial (Randomized Evaluation of Long-Term Anticoagulant Therapy). Issue 8 (23rd August 2016) - Ezekowitz, Michael D.; Nagarakanti, Rangadham; Noack, Herbert; Brueckmann, Martina; Litherland, Claire; Jacobs, Mark; Clemens, Andreas; Reilly, Paul A.; Connolly, Stuart J.; Yusuf, Salim; Wallentin, Lars
Abstract : Background: The RE-LY trial (Randomized Evaluation of Long-Term Anticoagulant Therapy) compared dabigatran 150 and 110 mg twice daily with warfarin in 18 113 patients with atrial fibrillation. Those with prosthetic heart valves, significant mitral stenosis, and valvular heart disease (VHD) requiring intervention were excluded. Others with VHD were included. Methods: This is a post hoc analysis of the RE-LY trial. Results: There were 3950 patients with any VHD: 3101 had mitral regurgitation, 1179 with tricuspid regurgitation, 817 had aortic regurgitation, 471 with aortic stenosis, and 193 with mild mitral stenosis. At baseline, patients with any VHD had more heart failure, coronary disease, renal impairment, and persistent atrial fibrillation. Patients with any VHD had higher rates of major bleeds (hazard ratio [HR], 1.32; 95% confidence interval [CI], 1.16–1.5) but similar stroke or systemic embolism event rates (HR, 1.09; 95% CI, 0.88–1.33). For patients receiving dabigatran 110 mg, major bleed rates were lower than for patients taking warfarin (HR, 0.73; 95% CI, 0.56–0.95 with VHD; HR, 0.84; 95% CI, 0.71–0.99 without VHD), and major bleed rates for dabigatran 150 mg were similar to those for warfarin in patients with VHD (HR, 0.82; 95% CI, 0.64–1.06) or without VHD (HR, 0.98; 95% CI, 0.83–1.15). For dabigatran 150 mg, stroke/systemic embolic event rates were lower compared with warfarin in those with VHD (HR, 0.59; 95% CI, 0.37–0.93) and those without VHD (HR, 0.67; 95% CI, 0.52–0.86), and stroke/systemic embolic event rates were similar for warfarin and dabigatran 110 mg regardless of the presence of VHD (HR, 0.97; 95% CI, 0.65–1.45; and HR, 0.88; 95% CI, 0.70–1.10). Intracranial bleeds and death rates for dabigatran 150 and 110 mg were lower compared with warfarin independently of the presence of VHD. Conclusions: The presence of any VHD did not influence the comparison of dabigatran with warfarin. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00262600. Abstract : Supplemental Digital Content is available in the text.